Fatores de personalidade e percepção de risco podem predizer o comportamento de risco? Um estudo com universitários - Mundim-Masini, Amanda Almeida (2009)
The risk is a subjective construct with different sense for different people, as well as the perception of its occurrence probability. The risk may be influenced for some psychological, social, institutional and cultural factors. Although the risk perception may be understood as an analytical information processing, it is necessary to consider the influence of experiential questions, guided by emotional and affective processes. Risk behavior is any action with at least an uncertain consequence that may be positive or negative. One of the objectives of the decision theory is to study and provide strategies for decisions under risk conditions and uncertainty that help people to reach satisfactorily their objectives and expectations. This study aimed to investigate the impact of personality and risk perception on risk behavior, as well as the impact of personality on risk perception. The research had a sample of 122 university students. To identify the relationship among the variables, data were submitted to multiple and linear regressions and correlation analysis. To verify possible differences among the students sub-samples from biomedical, exact and human sciences, data were submitted to variance analysis. The results point personality as better predictor of risk behavior than risk perception. Moreover, personality also predicts risk perception. The affective answer to the risk, investigated in this study through personality traits, is important in judgment process. Finally, there was not significant difference among the sub-samples in the variables factors (personality traits, risk behavior and risk perception), except in the factor socialization, in which students from biomedical science presented a superior average. Results suggest the necessity of taking into account cognitive and affective aspects in the studies of decision making process and judgment under risk.